Development and validation of the Mother's Socioemotional Support Circle (MSSC): A self-evaluation social support tool to guide social support efforts for preterm mothers in the NICU - Robert J. Ludwig; Judy Austin; Lianne J. Woodward; Laura C. Adams; Marc E. Jaffe; Michael M. Myers; Martha G. Welch (Acta Psychologica, 2025)
Emotional support from others plays a major role in a mother's ability to connect emotionally with her infant, particularly in the stressful context of preterm birth. Here, we document the development and validation of a novel assessment tool, the Mother's Socioemotional Support Circle (MSSC). The MSSC is a self-report instrument designed to assess the perceived availability and helpfulness of the mother's socioemotional support network. First reduced the number of items on the MSSC using methods based on item response theory and classical test theory. This analysis resulted in identifying 13 prospective core individuals in the mother's support circle. We then evaluated the reliability and construct and predictive validity of MSSC scores using data collected in the course of a clinical trial undertaken in a neonatal intensive care unit. We hypothesized that higher MSSC scores would be associated with lower levels of maternal anxiety and depression, and higher self-efficacy. Results showed that the MSSC had good internal consistency (Cronbach's α = 0.84), construct validity, confirmed through significant inverse correlations with depressive symptoms (CES-D: r = −0.30, p < 0.05) and state anxiety (STAI: r = −0.31, p < 0.01). Higher MSSC scores at baseline were also predictive of fewer maternal symptoms of depression at 12 months (CES-D: r = −0.29, p < 0.05) and greater maternal self-efficacy (MSES: r = 0.34, p < 0.01). Our findings support the MSSC's utility as a short, clinically effective tool for proactively guiding maternal support efforts in the neonatal setting.